Waiting for the pinewood: The Parc du Grand Pré and managing the extended time frames of a landscape project. Issue 1 (2nd January 2017) - Keravel, Sonia
Abstract: The Parc du Grand Pré in Langueux was awarded the Grand Prix National du Paysage of France in 2012. This project is exemplary for several reasons. First of all, it is a park that was designed in conjunction with the urban reorganization of the municipality and as a green corridor leading towards the sea, thus linking the centre of the town with the bay of Saint-Brieuc. Secondly, the project is imbedded within the lines of force of the area. It reveals the microgeographic dimension of the site with the small valley in which it lies and draws inspiration from the surrounding landscape. And finally, because the ecological dimension is so prevalent in the park, it fulfils an especially pedagogical role. The most emblematic of these ecological experiences is that of the pinewood plantation. In this article, we show how the spectacular mise en scène of this future wood generates an expectation among visitors and invites them to experience the extended, multiple time frames of the landscape project.